Temporal Changes of Seismic Velocity Caused by Volcanic Activity at Mt. Etna Revealed by the Autocorrelation of Ambient Seismic Noise - De Plaen, Raphael S. M.; Cannata, Andrea; Cannavo', Flavio; Caudron, Corentin; Lecocq, Thomas; Francis, Olivier (Frontiers in Earth Science, 2019)
On active volcanoes, ambient noise-based seismic interferometry, able to detect very slight variations in seismic velocity associated with magma transport towards the surface, can be a very useful monitoring tool. In this work, we performed the autocorrelation of ambient seismic noise recorded at Mt. Etna volcano, by three stations located close to the active summit craters, during April 2013 - October 2014. Such an interval was chosen because of the number and variety of eruptions. The method implemented to perform autocorrelation was the phase cross-correlation, which does not require normalization of the signals. The detected seismic velocity variations were very consistent for all three stations throughout the study period, mainly ranging between 0.3 and -0.2%, and were time-related to both sequences of paroxysmal eruptions and more effusive activities. In particular, we observed seismic velocity decreases accompanying paroxysmal eruptions, suggesting an intense pressurization within the plumbing system, which created an area of extensional strain with crack openings. It is worth noting that classical cross-station approach failed to detect seismic velocity changes related to volcano activity. In addition, seismic velocity variations over time were integrated with ground deformation data recorded by GPS stations and volcanic tremor centroid locations. Finally, we showed that, although the investigated frequency band (1-2 Hz) contains most of the volcanic tremor energy, our results did not indicate a particular contamination of seismic velocity variation measurements by variations of tremor sources.